Evaluasi Dampak Pembangunan Ekonomi Bagi Kesejahteraan Masyarakat di Wilayah Kabupaten - Irma Suryahani; Sri Murni (EKO-REGIONAL, 2006)
Evaluation is the part of activities development management to know how the activities development works.  Evaluation could be good or bad is depending on the inputs of the monitoring systems.  That is aim of this research.  By compare indicator descriptions using; Location Quotient, Shift Share and Williamson Index, this research is analyzed.  The conclusion is that Purbalingga’s PDRB in 2003 1.3 % increase.  Although the economic structure, in other side, gap among sectors are low.  It means each sector works better and relatively spread evenly.  That’s why the policy of budget allocation is better to interrelatedness (backward and forward) to each sector.Keywords: Evaluation, Shift Share, Williamson Index